A study on geriatric patients attending emergency department Hospital Universiti Sains Malaysia - Sjahid, Afifah Sjamun (2017)
This study aimed to determine the proportion of geriatric patients attending Emergency Department in Hospital Universiti Sains Malaysia (USM) within January 2015 to March 2015, the mean duration of hospital stay and the outcome of the illness in geriatric patients admitted to Hospital USM. This study also aimed to identify the associated factors of mortality in geriatrics patients admitted to Hospital USM. This study was a retrospective cohort study from January 2015 till March 2015 at Emergency Department Hospital USM. All patients aged 60 years and above attended Emergency Department of Hospital USM from January 2015 until March 2015 were included. Systematic random sampling was used. A total of 209 patients had been included in this study. Descriptive statistics were expressed as cross-tables for categorical variables and as mean ± standard deviation for numerical variables. Independent categorical variables were compared using Chi-Square test or Fisher’s exact test. Paired group comparisons were performed using Independent t-test or Mann Whitney test for numerical variables. Total patients included in this study were 209 patients. The mean (standard deviation, SD) age was 68.4 (6.95) years old, with age range from 60 till 106 years old. Fifty-eight percent were male and 95.7% were Malay. Seventy-eight percent were triaged as an emergency; with 19.6% were red zone cases, while 51.2% were yellow zone cases. Three most common presenting symptoms were respiratory symptoms (24.9%), cardiovascular symptoms (19.65%) and gastrointestinal symptoms (12.9%). Out of209 patients studied, 95 patients (45.5%) were admitted. Mean duration of hospital stay was 8 days (mean 7.57, SD 12.97). Out of 95 patients admitted, only 15 patients (15.8%) died in the ward. Factors associated with mortality in hospitalized geriatric patients were gender (p = 0.009), patient’s method of arrival (p = 0.001), conscious level on arrival (p < 0.001), patient’s condition when transferring to the ward; either ventilated (p = 0.014) and on inotropic agent (p < 0.001) or not, patient’s first pulse rate taken at triage (p < 0.001) and first blood investigations taken in emergency department; white blood cell (p = 0.007), hemoglobin (p = 0.019), serum lactate (p < 0.001) and serum urea (p = 0.036). Majority of the geriatric patients triaged as emergency cases indicated that they mostly came with ill-conditioned that need to be attended immediately. By knowing the common presenting symptoms and associated factors of mortality in admitted geriatric patients will alert medical personnel in the emergency department to treat this group of patients more thoroughly and judiciously.